A Constructivist Perspective on the Shi'a Sources of Seyyed Haydar Amoli's Mystical Experiences - Iman Ghorbani gulogerdi; Manouchehr Joukar; Adel Sawaedi; Davood Poor mozaffari (ادبیات عرفانی, 2025)
Seyyed Heydar Amoli, a mystic of the eighth century AH, reports some of his mystical experiences in the book "Nass al-Nusus fi Sharh al-Fusus". In these experiences, he perceives that the names of the Prophet (PBUH) and the Imams (AS) are written in the sky with colorful lights. An important question is why his experiences are formed and described in this way. From a constructivist perspective, all people's experiences, including those of mystics, are contextual and constructed within their religious and social conceptual frameworks. This article, attempts to answer to this question through a descriptive-analytical examination of Shi'i narratives in their historical and social context. Our investigations indicate that there are overlaps between Seyyed Heydar’s experiences and some Shi'i narratives about the "Cosmic Creation of the Prophet (PBUH) and the Imams (AS)," "their position on the throne," and "the writing of their names on the throne." From a constructionist perspective, Seyyed Heydar Amoli’s experiences are contextual. These experiences are considered pure and originate from his specific mystical state, rather than being created within a conceptual framework. Instead, they are the product of intertextual relationships with Shiite narrations, traditions, and previous interpretations, and are constructed through the conceptual framework of these narratives.